Librarians' nonverbal communication in user services at the University of Pamulang Library - Dina Rahadatul Hasanah; Nurul Hayati (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. This study examines the nonverbal communication of circulation librarians at Universitas Pamulang (UNPAM) Library, prompted by user complaints of unfriendly expressions, minimal eye contact, and reluctant body language. The research aims to understand how librarians use nonverbal cues when serving users. Methods. A qualitative case study approach was employed, using observation, interviews, documentation, and literature review with four users and one librarian. Data validity was ensured through triangulation. Analysis involved data reduction, display, and conclusion, interpreting nonverbal elements (gestures, facial expressions, posture) using kinesics theory. Results and Discussion. Librarians used head orientation, hand gestures, facial expressions, and posture to convey attentiveness and professionalism. Eye contact was maintained through head direction, gestures guided users, and body position fostered comfortable interactions. However, high workload occasionally impacted the quality of these nonverbal cues. Conclusion. Nonverbal communication significantly influences user perceptions and comfort during library services. Training in nonverbal communication and ergonomic workspace arrangements are recommended to enhance service quality.